In certain physics textbooks, one starts with the assumption (in a one linear and one time dimension) that 1) x2 - c2t2 = x'2 - c2t'2 I don't want to go into that. Let us start from there. Now, if you assume that 2) x = vt, then 3) x' = 0 always because the origin is moving at v along the x-axis so that x' is always zero. Using those three bits of information one can derive the Lorentz equations: x' = [tex]\gamma[/tex](x - vt) t' = [tex]\gamma[/tex](t - xv/c2) where [tex]\gamma[/tex] = SQRT[1 - v2/c2] (I can't get the square root to come out in LATEX) I have tried, tried, tried to do that but I cannot. Anyone can help? If I substitute the Lorentz equations back into the above three bits of information, it will work out but that's backwards. I want to do it forwards.